THE CRISIS OF THE BRAZILIAN PRISON SYSTEM IN THE PANDEMIC: THE CHALLENGES OF EDUCATION - Antonio de Jesus, Everaldo (Revista Gênero e Interdisciplinaridade, 2023)
This study deals with the theme of Education and the Brazilian Prison System based on the crisis generated by the COVID-19 pandemic. Now, it cannot be denied that Education has become a Fundamental Right. However, prisoners, in general, already have difficulties accessing this right in a so-called “normal” scenario. In the pandemic scenario, everything becomes more difficult. Even the basic conditions for maintaining the safety and life of those incarcerated were relegated, in several prisons in Brazil, to the background. Pedagogical practices in these prisons have become even more scarce. Therefore, this work seeks to investigate, even if briefly, how COVID-19 impacted Brazilian prisons and, also, the challenges it ended up generating for carrying out Education within prisons.